If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 7x + 1 = 4 + -2x Reorder the terms: 1 + 7x = 4 + -2x Solving 1 + 7x = 4 + -2x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '2x' to each side of the equation. 1 + 7x + 2x = 4 + -2x + 2x Combine like terms: 7x + 2x = 9x 1 + 9x = 4 + -2x + 2x Combine like terms: -2x + 2x = 0 1 + 9x = 4 + 0 1 + 9x = 4 Add '-1' to each side of the equation. 1 + -1 + 9x = 4 + -1 Combine like terms: 1 + -1 = 0 0 + 9x = 4 + -1 9x = 4 + -1 Combine like terms: 4 + -1 = 3 9x = 3 Divide each side by '9'. x = 0.3333333333 Simplifying x = 0.3333333333
| sin(x)*cos(4x)=sin(5x) | | 20x+30y=412.5 | | -42+10x=6x+70 | | 2x-5=61 | | z+7=4 | | 4.6z-6=3.6z-6 | | 21-4x=-27 | | 8x-4x+3x=7x+x+14 | | X^2=aX^2+25b^2-10ab | | 2x+12+9x-27=12+24 | | 8sqrtx=x+15 | | 2(4x+10)=8x+10 | | 7-12=-2 | | 7.6x+1=6.6x | | 3(3w-6)=8 | | x+6(x-1)=7 | | 5*5*8*8*5*5= | | -129+x=131+11x | | -3x-14=-8x+13 | | 26-b=39-9 | | 2x+1+x-3+44=180 | | -6+-2x=29+3x | | 63+5u=14u | | -4x-17=17-6x | | 7x^2-46x+5=0 | | -96-x=30-8x | | y-3=-1(x+9) | | -7p+16=2p+4+3p | | 7+4x=-2x+11 | | -96-2x=24-12x | | 0.5x+0.6(2x+1)=5.7 | | 25-x=y |